Identification and clinical implications of endogenous retrovirus elements suppressed by SETDB1 in hepatocellular carcinoma - Yosuke Igarashi; Yoshimitsu Akiyama; Shu Shimada; Shuichi Watanabe; Megumi Hatano; Keita Kodera; Kohei Okazaki; Yoshiaki Tanji; Shu Tsukihara; Tomohiko Taniai; Atsushi Nara; Masahiro Yamane; et al. (JHEP Reports)
Background & Aims: The inhibition of epigenetic regulators activates endogenous retrovirus (ERV) expression, which can stimulate a viral mimicry response in cancer cells. ERV elements are aberrantly expressed in hepatocellular carcinoma (HCC); however, the expression of ERVs regulated by histone modifications and their clinical significance in HCC remain unclear. Here, we identified specific human endogenous retrovirus (HERV) elements epigenetically suppressed by the histone methyltransferase SETDB1 in HCC. Methods: The Cancer Genome Atlas (TCGA) dataset was analyzed to identify HERV elements based on SETDB1 expression levels. SETDB1 knockdown (KD) was performed in mouse and human HCC cells to investigate the resulting biological effects and changes in HERV expression, both in vitro and in vivo. Results: TCGA analysis revealed an inverse correlation between SETDB1 and retroelements in human HCC (R = -0.723, p = 2.297 × 10-40), identifying four specific HERV elements in SETDB1-high expressing HCC cases. Low expression of these four HERVs was associated with poor prognosis, and their combined expression provided additional prognostic insight (p <0.001). Increased expression of the four HERV elements and decreased H3K9me3 levels at these regions were detected in human HCC cells with SETDB1-KD. In murine HCC cells, Setdb1-KD impaired in vivo tumor growth with increasing CD8-positive T-cell infiltration. Moreover, the interferon α response pathway and multiple ERV elements were activated in mouse HCC cells with Setdb1-KD. The expression of interferon-stimulated genes, as indicators of a viral mimicry response, was elevated in both murine and human SETDB1-KD HCC cells. Conclusions: The suppression of four novel HERV elements by SETDB1 serves as a prognostic marker in HCC. Activation of these SETDB1-regulated HERVs could represent a promising therapeutic strategy for HCC. Impact and implications:: An inverse relationship between retroelements including human endogenous retrovirus (HERV) elements and SETDB1 expression was observed in human hepatocellular carcinoma (HCC) by The Cancer Genome Atlas data analysis. We identified four HERV elements downregulated by SETDB1-dependent H3K9me3 in HCC cells, with low expression levels of these HERV elements correlating with poor prognosis in patients with HCC. SETDB1 depletion resulted in upregulation of various interferon-stimulated genes associated with viral mimicry in HCC cells. These findings suggest that the four SETDB1-regulated HERVs could serve as prognostic markers and potential therapeutic targets for HCC.